A Novel Polysaccharide Depolymerase Encoded by the Phage SH-KP152226 Confers Specific Activity Against Multidrug-Resistant Klebsiella pneumoniae via Biofilm Degradation - Wu, Yunqiang; Wang, Rui; Xu, Mengsha; Liu, Yanan; Zhu, Xianchao; Qiu, Jiangfeng; Liu, Qiming; He, Ping; Li, Qingtian (Frontiers in Microbiology, 2019)
The increasing prevalence of infections caused by multidrug-resistant Klebsiella pneumoniae necessitates the development of alternative therapies. Here, we isolated, characterized, and sequenced a K. pneumoniae bacteriophage (SH-KP152226) that specifically infects and lyses K. pneumoniae capsular type K47. The phage SH-KP152226 contains a genome of 41,420 bp that encodes 48 predicted proteins. Among these proteins, Dep42, the gene product of ORF42, is a putative tail fiber protein and hypothetically possesses depolymerase activity. We demonstrated that recombinant Dep42 showed specific enzymatic activities in the depolymerization of the K47 capsule of K. pneumoniae and was able to significantly inhibit biofilm formation and/or degrade formed biofilms. We also showed that Dep42 could enhance polymyxin activity against K. pneumoniae biofilms when used in combination with antibiotics. These results suggest that combination of the identified novel depolymerase Dep42, encoded by the phage SH-KP152226, with antibiotics may represent a promising strategy to combat infections caused by drug-resistant and biofilm-forming K. pneumoniae.